Wireless User Interface Devices for Connected Intelligent Environments - Wilson, Andy (Ubicomp 2003 Workshop on Multi-Device Interfaces for Ubiquitous Peripheral Interaction, 2003)
We present the XWand, a hardware device and associated signal processing algorithms for an interface that may control multiple connected devices in a natural manner. The main idea is that the user should merely point at the device to be controlled, and use simple gestures or speech to control the device. The intelligent environment system interprets the user’s manipulation of the wand to determine an appropriate action in context. The ultimate goal of such a natural interface is to provide an interface that is so simple that it requires no particular instruction or special knowledge to use, and instead relies on the intelligence of the environment to figure out what to do.